Pelaksanaan Kurikulum Merdeka di SD Negeri 2 Manurunge Kecamatan Tanete Riattang Kabupaten Bone - Sudarto Sudarto; Moh. Noridwan; Muhammad Amin (Journal on Education, 2023)
This research is a qualitative research that aimed to find out the description of Kurikulum Merdeka Implemetation at SD Negeri 2 Manurungge Watampone, especially in grades I and as the Class that was pointed to implementate the Kurikulum Merdeka at the school mentioned. There were 3 perssons to be subjects in this study, namely the headmaster, homeroom teacher for Grade I, and Class teacher for Grade IV at SD Negeri 2 Manurungge. Data collection techniques used in this study were interviews, observation, and document studies. Data analysis techniques include : data reduction, data display and drawing conclusions. The results of this study indicated that: (1) the implementation of the Kurikulum Merdeka at SD Negeri 2 Manurungge has been going well. The learning applied by the teacher was in line with the expectations of the Kurikulum Merdeka, (2) the teacher has prepared a learning plan based on teaching modules, (3) the teacher has planned and implemented the student-centered learning and the differentiated learning. However, in the aspect of differentiation learning, the implementation has not been maximized, the teacher has not implemented task/project differentiation perfectly. Conclusion: in general, SD Negeri 2 Manurungge as a school implementator the Kurikulum Merdeka has implemented the Merdeka Curriculum well. However, the Class teachers implementing of the Kurikulum Merdeka are expected to continue and improve the quality of implementation of the curriculum, especially in a differentiated learning process.